Creating large 60Co-γ populations for functional genomics and breeding in wheat - Hao, Qunqun; Ma, Simeng; Zhang, Jifa; Wang, Yuhai; Wang, Wenqiang (Frontiers in Plant Science, 2026)
Wheat (Triticum aestivum L.) serves as a critically important staple crop worldwide, and mutation breeding through Cobalt-60 (60Co-γ) radiation has been widely adopted as an effective strategy for genetic improvement. In this study, ten wheat cultivars from Shandong, Henan, and Hebei were subjected to 60Co-γ irradiation to develop an M2 mutant population comprising 10,350,000 lines. Systematic screening M2 mutant population under natural conditions identified 158 freezing-tolerant mutants, 441 saline-alkali-tolerant mutants, and >5,000 mutants with changed yield or quality traits. This population represents a valuable genetic resource for collaborative research and provides a powerful platform for functional genomics studies and breeding applications.